Investigating the role of angiogenesis in systemic lupus erythematosus. (May 2015) - Liu, J; Wang, X; Yang, X; Yan, Q; Wang, S; Han, W
Objective: We aimed to elucidate the roles of six pro-angiogenic factors, namely, basic fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF), placental growth factor (PlGF), hepatocyte growth factor (HGF), transforming growth factor-beta (TGF-beta) and tumor necrosis factor-alpha (TNF-alpha), in the pathogenesis of systemic lupus erythematosus (SLE). Methods: A group of 75 patients with SLE and a control group of 40 healthy volunteers were recruited. Angiogenic factors were tested through enzyme-linked immunosorbent assay (ELISA) measurement. The angiogenic activities of the patients with SLE and the healthy controls were assessed and a correlation analysis of these angiogenic factors was conducted. Results: A much higher level of angiogenic activity was shown in the serum of patients with SLE than that of the healthy controls, yet no statistically significant difference was found in the angiogenic activities of active SLE and inactive SLE. Serum VEGF level in the active SLE group was significantly higher than that in the control group and the inactive SLE group, and serum HGF level was strongly positively correlated with VEGF in all SLE groups; meanwhile, there was also a statistically significant positive correlation between TNF-alpha and VEGF in all SLE groups. There was a statistically significant positive correlation between serum VEGF level and bFGF level in the active SLE group. There was a slightly negative correlation between serum HGF level and TGF-beta level in the SLE group, but this negativity did not reach the significance level. Likewise, positive correlation was also shown in the serum VEGF level and PlGF level, yet not in bFGF with PlGF. Conclusion: Circulating serum angiogenic cytokines may be disease markers of SLE activity. Anti-angiogenic agents such as thalidomide and endogenous angiogenesis inhibitors such as endostatin are potentially effective and promising therapies in the treatment of SLE.